Development of soil organic matter measurement system - Áron Béni; Evelin Juhász; Péter Ragán; Tamás Rátonyi; Gábor Várbíró; István Fekete (Soil and Water Research, 2021)
We managed to create a self-developed sensor system, which is based on the simultaneous reflectance measurements at a 660 and 940 nm wavelength. The ratio of the reflectance refers to the concentration of the soil organic carbon (SOC). This instrument has a calibration range of 1.19 to 6.05 SOC%. The SOC content of twenty-six soil samples was measured by the self-developed system and a standard spectrophotometric method and we found that the SOC estimation in the self-developed system had a good approximation and the differences ranged from -27.72% ~ + 6.99%. We found a strong correlation between the data of the reference measurements (R2 = 0.73) and the values indicated by our self-developed sensor system (Reference (SOX%) =1.4857 × E (SOC%) - 0.7393). This measurement system is easy to use and displays and records the data in real time. This allows one to map an agricultural production area based on the SOC concentration using its built-in GPS unit.